Production and characterization of biopowders made from gel-forming polymers - Chan, Eng Seng; Sariah Abang; Rachel F. Mansa; Pogaku Ravindra (Universiti Malaysia Sabah, 2007)
To date, many bioactive compounds have been encapsulated within microparticles to achieve specific purpose such as stabilization, protection, isolation, controlled-release, taste-masking, improving aesthetic and handling qualities. However, much work is still needed particularly to determine the way to control the size and shape of microparticles produced using the air-atomization method. In addition, the effect of drying on the properties of dried biopowders has yet to be evaluated. These problems form the missing gap that will be addressed by this project. In this work, alginate was chosen as a model polymeric material to form the biopowders. The first part of this work was to determine the key physical properties of the polymer solution since they have significant influence on the characteristics (i.e. size) of the particles formed. The density of Na-alginate solution increased slightly as the alginate concentration increased whereas the solution apparent viscosity at zero shear rates exhibited a typical exponential increment. A new method, LCP coefficient method, to measure surface tension of viscous biopolymer solutions has been developed. The surface tension at low alginate concentration (5 -20 g/L) was about 68 -72mN/m and it showed a decreasing trend as the concentration increased. Air-assist external mixing atomization with low mair/rituqwas developed to produce wet particles of wide range of mean diameters, from 50 to 2300 µm. A semi-empirical size prediction model was developed to assist and enhanced the productivity of desired size by changing the physical properties of the operating conditions. Increased in Weber number produced smaller particles size, wider particles size distribution and more spherical particles. Finally, biopowders were formed by drying the wet particles. The results showed that drying temperature, intermittent mixing, sample thickness and wet particle size were among factors affecting the drying kinetics. Effective diffusivity value of wet alginate particles was ranged from 5.4 x 10·10 to 8.0 x 10·9 m2/s while the activation energy was ranged from 15 to 20 KJ/mol. The drying kinetic was modelled according to a logarithmic model. In addition, smaller wet particles (75 µm) were found to agglomerate during the oven-drying process whereas larger particles (1300 µm) did not agglomerate. Freezedrying process did not cause agglomeration for both particle sizes. The type of drying method (oven-drying or freeze-drying) was found to have significant influence on the size, size distribution and physical appearance of the biopowders formed.